2021
DOI: 10.1016/j.kint.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The urgent need to vaccinate dialysis patients against severe acute respiratory syndrome coronavirus 2: a call to action

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 5 publications
1
90
0
8
Order By: Relevance
“…Few, if any, patient groups have been affected to the same extent as patients with chronic kidney disease (CKD). These patients have amongst the poorest of outcomes if they contract the virus and, in the case of patients on unit based haemodialysis (HD), have been unable to shelter in place to protect themselves [ 1 ] [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few, if any, patient groups have been affected to the same extent as patients with chronic kidney disease (CKD). These patients have amongst the poorest of outcomes if they contract the virus and, in the case of patients on unit based haemodialysis (HD), have been unable to shelter in place to protect themselves [ 1 ] [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The devastation of the COVID-19 (coronavirus disease 2019) pandemic has been rippling through the population of dialyzed patients. Previous studies have reported horrifyingly disproportionate age-adjusted rates of cases, with fatality rates varying from 16% to 32% deaths [ 1 , 2 ]. In the absence of an effective COVID-19 treatment, vaccination is the only chance to improve the extremely poor prognosis in this population.…”
Section: Introductionmentioning
confidence: 99%
“…To the editor: The coronavirus pandemic resulted in devastatingly high rates of infection and mortality (up to 20% and 32%, respectively) for patients receiving in-center hemodialysis (ICHD). 1 The arrival of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines was anxiously awaited. Large trials reported vaccine efficacy of 62% to 95%.…”
Section: Sars-cov-2 Vaccination Programmentioning
confidence: 99%
“…2,3 Data from other vaccines suggested benefit in kidney patients, despite attenuated immune responses. 4 Given the devastating toll of coronavirus disease 2019 (COVID-19), and the kidney community's call to action, 1 we advocated for urgent provision of SARS-CoV-2 vaccines for patients receiving ICHD.…”
Section: Sars-cov-2 Vaccination Programmentioning
confidence: 99%
See 1 more Smart Citation